2022
DOI: 10.3390/biomimetics7030136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of rmBMP-7 on Osteoblastic Cells Grown on a Nanostructured Titanium Surface

Abstract: This study evaluates the effects of the availability of exogenous BMP-7 on osteoblastic cells’ differentiation on a nanotextured Ti surface obtained by chemical etching (Nano-Ti). The MC3T3-E1 and UMR-106 osteoblastic cell lines were cultured for 5 and 7 days, respectively, on a Nano-Ti surface and on a control surface (Control-Ti) in an osteogenic medium supplemented with either 40 or 200 ng/mL recombinant mouse (rm) BMP-7. The results showed that MC3T3-E1 cells exhibited distinct responsiveness when exposed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(10 citation statements)
references
References 51 publications
(65 reference statements)
0
10
0
Order By: Relevance
“…To obtain Nano-Ti, commercially pure grade 2 Ti discs (Realum, São Paulo, Brazil), modified to exhibit a hollowed surface ( Figure S1 ), were cleaned by sonication and etched in a solution consisting of equal volumes of concentrated 30% H 2 O 2 and H 2 SO 4 (95–97%) for 4 h (10 mL/disc) at room temperature (RT) [ 12 , 20 ]. Then, they were rinsed in distilled water, air dried, and autoclaved.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations
“…To obtain Nano-Ti, commercially pure grade 2 Ti discs (Realum, São Paulo, Brazil), modified to exhibit a hollowed surface ( Figure S1 ), were cleaned by sonication and etched in a solution consisting of equal volumes of concentrated 30% H 2 O 2 and H 2 SO 4 (95–97%) for 4 h (10 mL/disc) at room temperature (RT) [ 12 , 20 ]. Then, they were rinsed in distilled water, air dried, and autoclaved.…”
Section: Methodsmentioning
confidence: 99%
“…The strategies used to functionalize with BMP-7 involve modifications of the biomaterial surface chemistry and topography at a nanoscale, including those of metals [ 8 , 9 , 10 , 11 ]. In a previous initial study, we observed that the effects of providing 40 and 200 ng/mL of a recombinant mouse (rm) BMP-7 to osteoblastic cells grown on titanium (Ti) were modulated by the nanotopographic features of its surface, with an increased expression of the osteoblast markers osteopontin (OPN) and alkaline phosphatase (ALP), but without enhancement in the mineralized matrix formation [ 12 ]. Interestingly, the Ti nanotopography (Nano-Ti) per se (without rmBMP-7 in the culture medium) promoted osteogenic differentiation compared with an almost flat surface at a nanoscale [ 12 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, there are no uniform results regarding the osteogenic power of BMP-7-functionalized Ti; an in vitro study by Togashi et al (2009) found no effect of the addition of rhBMP-7 to the culture medium on the viability, proliferation, or differentiation of osteoblastlike cells, whereas others have found superior osteogenic power of samples with BMP-7 (Cirano et al, 2014). Zuardi et al (2022) in a recent study, demonstrated that the effects of BMP-7 on osteogenic differentiation in vitro, would be conditioned by the topography of the surface on which the cell cultures are grown, the concentration of the growth factor in the culture medium and the stage of differentiation of the osteoblastic cells. Chen et al (2013) developed a BMP-7-activated Ti gene delivery system for in vitro osteoblast culture and found enhanced differentiation capacity.…”
Section: Figurementioning
confidence: 99%